THE LATEST TECHNOLOGIES OF AUTOMATIC WELDING OF THE COMPANY CRC - Martyniuk, R. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Currently, welding is one of the most common technologies for joining metal parts in many branches of modern industry. Its wide application is due to a number of advantages, such as reducing the weight of structures, reducing the time for manufacturing products of complex shape, great opportunities for mechanization and automation of the process. Automation of the welding process is a promising direction of welding production. Automatic welding, today, has the best combination of such indicators as: the quality of finished welded joints, the productivity of the welding process, as well as the economic efficiency of application. In addition, the undoubted advantage of using automatic welding technology in shielding gases in the construction of main pipelines is the full automation of the welding process, which provides high productivity for a wide range of pipe sizes being welded in combination with high mechanical properties of welded joints. The introduction of an automatic welding method minimizes the amount of deposited metal, which, in addition to saving welding materials, reduces the time for manufacturing welding materials. The use of new technology minimizes the impact of the human factor on the welding process, and also facilitates the training of welders, which ultimately increases the mechanical properties of welded joints and ensures the stability of their production.